Physical Activity, Obesity, Family History, and Their Associations with Hypertension among the Elderly in Aceh Singkil, Aceh - Ricca Nophia Amra; Fazidah Aguslina Siregar; Erna Mutiara (Journal of Epidemiology and Public Health, 2020)
Background: Hypertension is an important global health challenge due to its high prevalence and resulting cardiovascular disease and chronic kidney disease. This study aimed to examine the associations of physical activity, obesity, family history, with hypertension among the elderly in Aceh Singkil, Aceh.Subjects and Method: This was a case control study carried out in Aceh Singkil, Aceh, Indo